(untitled) (Global Journal of Medical Research, 2024)
Background: Traumatic injuries are the leading cause of death in the age group of 1 to 45 years in the United States of America and globally in the age group of 15 to 49 years. The World Health Organization (WHO) estimates that almost 90% of deaths caused by trauma occur in low-or middle-income countries, where 85% of the world’s population. The primary aim is to assess the safety of barbiturate coma use in traumatic brain injury (TBI) patients without invasive intracranial pressure monitoring. The study aimed to investigate etiological factors, health outcomes, and the effects of barbiturate infusion on neurotrauma and describe the characteristics of the TBI population. Data from 55 patients with isolated severe TBI were analysed.